الزراعة المائية في ليبيا التحديات والفرص - حسن عمران الصويعي الرقيعي (Surman Journal of Science and Technology, 2024)
Hydroponics is regarded as one of the promising advancements in agricultural industry providing a rather effective answer to ecological and agricultural problems, including the shortage of fresh water in many countries including Libya. Hence, this research seeks to examine the viability and prospects for hydroponic systems in Libya as well as present a legal and policy framework to foster its use. Leisurely reading the existing body of literature and conducting 1:1 interview with the specialized professionals, the broad range of problems and prospects associated with the hydroponics’ application, embracing environmental and economic impacts, technological uses of hydroponics, and the challenges encountered on the way to implementing these systems, were outlined. The study established that the use of hydroponics easily enhances food security in Libya through increased on water usage as well as increasing food production. Nevertheless, further development of this sector implied further governmental support, which should promote the formation of incentive policies encouraging the utilization of further advanced technologies. Also, there are serious requirements for development of large-scale infrastructure and development of personnel upgrade programs as a result of which local capabilities should be improved significantly. The research underscores the need for a clear and coherent political and regulatory agenda through which progress toward more sustainable forms of agriculture can be enabled and into which innovation and investment priorities can be directed. These findings therefore present a useful starting point for managers and investors interested in approaching hydroponics in Libya systematically.